Impacts of Different Angles and Speeds on Behavior of Pedestrian Crowd Merging. Issue 1 (January 2015) - Aghabayk, Kayvan; Sarvi, Majid; Ejtemai, Omid; Sobhani, Amir
Many forms of complex pedestrian crowd behaviors, including merging, can be identified in built environments such as public transport stations and public buildings. Understanding and capturing this phenomenon in a robust model is a challenging task; it is also a significant opportunity for research, given the international demand for models of this type. Despite the frequent occurrence of merging of crowd streams, this complex behavior has not received enough attention so far. The literature that is related to crowd merging is limited to T-shaped intersections and studies conducted on staircases. In this study using experimental data, the crowd merging phenomenon was investigated. The impacts of different merging angles and different pedestrian speeds were investigated. The results showed that flow rates and headway distributions are affected by variety in pedestrian speeds and merging angles.